Evaluating Competition Strategies for Generic Drug Industries Using Game Theory - A supplement to report “Scenario Planning as a Tool for Long Term Strategic Planning” - Khan, Ali Zafar (2010)
This report is a supplement to the project titled “Scenario Planning as a Tool for Long Term Strategic Planning - The Generics Drug Industry in the European Union.” The report will further evaluate the resultant scenarios and strategies build and recommended as part of the titled project mentioned above. Game theory perspectives will be used as a tool to analyse how economic agents (stakeholders of the pharmaceutical generic drugs industry) will react when what they do affects the actions of others. The report will evaluate hypothetical actions taken by generic drugs industry players and their outcomes/payoffs relative to the competitions. It will draw on strategic and extensive forms of games to identify how to act and how to think about your rival’s actions. What would be a more powerful in business strategy than this?